Effect of salinity on the rearing performance of juvenile golden pompano Trachinotus ovatus (Linnaeus 1758). (27th October 2014) - Ma, Zhenhua; Guo, Huayang; Zheng, Panlong; Wang, Long; Jiang, Shigui; Zhang, Dianchang; Qin, Jian G
Abstract: Effect of rearing salinity on the performance of juvenile golden pompano Trachinotus ovatus (Linnaeus 1758) was studied under a laboratory condition. Fish growth, survival, RNA/DNA ratio, pepsin activity, α‐amylase activity and FCR were used as evaluation criteria. The growth and RNA/DNA ratio were significantly affected by the rearing salinity. High growth rate and RNA/DNA ratio were observed when fish were reared at the salinity of 34‰. The pepsin activity of fish was not significantly affected by the rearing salinity. However, the α‐amylase activity of fish was significantly affected by the rearing salinity. The α‐amylase activity of fish reared at the salinity of 10‰ was significantly lower than fish cultured at the salinity of 34‰. Rearing salinity can significantly affect the FCR of juvenile golden pompano. The FCR of fish cultured at the salinity of 10‰ was 5‐times higher than the FCR of fish reared at 34‰. Results from the present study indicate that juvenile golden pompano can be reared above 26‰ without affecting fish performance, and the salinity of 10‰ may be too low to rear juvenile golden pompano as fish growth, RNA/DNA ratio and α‐amylase activity were reduced.